Investigating Seasonal Succession Patterns in Mesozooplankton Community Structure Following Hurricane Harvey - Topor, Zachary M.; Robinson, Kelly L.; Turcu, Andrea (Frontiers in Marine Science, 2020)
The northern Gulf of Mexico (nGOM) is a highly productive region and supports some of the world’s largest fisheries. Mesozooplankton represent a key linkage in coastal food webs for larval fish, both as food and as competition. While many studies have investigated seasonal patterns of mesozooplankton off the Louisiana coast and in the Mississippi Bight, there is little information about mesozooplankton communities off the Texas coast. In this study, we investigated environmental drivers of mesozooplankton community variability over space and time. Samples were collected on the Texas shelf near Galveston Bay at seasonal intervals following Hurricane Harvey. Total mesozooplankton abundance were found to be highest in September. Diversity exhibited a hump-shaped pattern over the six months sampled, with the highest diversity occurring in October 2017. Taxa richness did not vary over the sampling period. Significant differences in mesozooplankton community structure were found only between Sept 2017 and Mar 2018. Community abundance was greatest nearshore, and zooplankton diversity was greatest on the shelf. Abundance was found to be driven by temperature while community composition was found to be related to salinity. Spatial and temporal patterns of specific larval fish prey are presented.